Lovers at the chameleon club, paris 1932 ebook A novel. - Prose, Francine (2014)
A richly imagined and stunningly inventive literary masterpiece of love, art, and betrayal, exploring the genesis of evil, the unforeseen consequences of love, and the ultimate unreliability of storytelling itself. Paris in the 1920s shimmers with excitement, dissipation, and freedom. It is a place of intoxicating ambition, passion, art, and discontent, where louche jazz venues like the Chameleon Club draw expats, artists, libertines, and parvenus looking to indulge their true selves. It is at the Chameleon where the striking Lou Villars, an extraordinary athlete and scandalous cross-dressing lesbian, finds refuge among the club's loyal denizens, including the rising Hungarian photographer Gabor Tsenyi, the socialite and art patron Baroness Lily de Rossignol; and the caustic American writer Lionel Maine. As the years pass, their fortunes—and the world itself—evolve. Lou falls desperately in love and finds success as a race car driver. Gabor builds his reputation with startlingly vivid and imaginative photographs, including a haunting portrait of Lou and her lover, which will resonate through all their lives. As the exuberant twenties give way to darker times, Lou experiences another metamorphosis—sparked by tumultuous events—that will warp her earnest desire for love and approval into something far more.